Peasants, culture and Indigenous peoples : critical issues - Stavenhagen, Rodolfo (SpringerBriefs on pioneers in science and practice. Texts and protocols ;, 2013)
This last volume in a trilogy published on the occasion of the 80th birthday of Rodolfo Stavenhagen, professor emeritus of El Colegio de Mexico, includes eight essays on Peasants, Culture and Indigenous Peoples: Critical Issues; Basic Needs, Peasants and the Strategy for Rural Development (1976); Cultural Rights: a Social Science Perspective (1998); The Structure of Injustice: Poverty, Marginality, Exclusion and Human Rights (2000); What Kind of Yarn? From Color Line to Multicolored Hammock: Reflections on Racism and Public Policy (2001); The United Nations Special Rapporteur on the Rights of Indigenous Peoples (2012); A Report on the Human Rights Situation of Indigenous Peoples in Asia (2007); Report on the Impact of Megaprojects on the Rights of Indigenous Peoples (2003); and Study Regarding the Best Practices to Implement the Recommendations of the Special Rapporteur (2007). These texts address human rights issues, especially those that arose when Stavenhagen was servinged as United Nations special rapporteur on the rights of Indigenous peoples.